Spread of the Sindbis Virus in Fennoscandia - L. V. Rubis (Проблемы особо опасных инфекций, 2023)
In the second half of the last century, a persistent focus of the disease caused by Sindbis virus was formed on the territory of Fennoscandia. In different countries, the disease is called Pogosta disease, Ockelbo disease and Karelian fever. The highest incidence rate is in Finland, where diseases are recorded annually, ranging from sporadic cases to large outbreaks with hundreds of patients. In other Scandinavian countries and in Russia, isolated cases of infection are currently being detected. The data on registered incidence and the results of seroepidemiological studies indicate an unequal dissemination of the infection in Fennoscandia, the causes of which need to be investigated. The review presents updated information on the pathogen, its distribution among the population and in the biocenosis of Fennoscandia, clinical features, diagnostics and epidemiological characteristics of the incidence.